Pediatric reference values of anterior visual pathway structures measured with axis-correction on high-resolution 3D T2 fast spin echo sequences - Stefan Markart; Simon Wildermuth; Johannes Geiss; Erik P. Willems; Veit Sturm; Michael Ditchfield; Stephan Waelti (BMC, 2022)
Abstract Background The size of the anterior visual pathway (AVP) structures is affected by patient age and pathology. Normative data is useful when determining whether pathology is present. AVP structures do not respect the standard planes of magnetic resonance (MR) imaging. The aim of this study was to produce normative age-related and axis-corrected data of the AVP structures using multiplanar reformation (MPR) of high-resolution 3D T2-weighted fast spin echo (3D T2w FSE) images. Methods For each patient 32 measurements of AVP structures were obtained in 145 children (2 months - 18 years) with normal brain MR studies on high-resolution 3D T2w FSE images adjusted to the axis of each AVP structure. Descriptive statistics were calculated for different age classes and growth models were fitted to the data and assessed for their performance to create a formal statistical model that allows inference beyond the sample. Results Descriptive statistics were compiled in a reference table and prediction plots in relation to age, height, and body surface area (BSA) were obtained from the best overall performing statistical model, also taking field strength (1.5 vs. 3 T) into account. Intraclass correlation coefficient values were calculated for all variables ranging from 0.474 to 0.967, the most reliable being the transverse diameter of the globe, the maximum diameter of the retrobulbar nerve sheath, the intracranial segment of the optic nerve and the transverse diameter of the chiasm. The maximum retrobulbar diameter of the optic nerve sheath and the lateral superoinferior diameter of the chiasm showed no statistically significant change with age. Conclusion Detailed charts of reference values for AVP structures as well as prediction plots in relation to age, height and BSA were established using axis-corrected measurements from the MPR of high-resolution 3D T2w FSE images. Furthermore, an Excel spreadsheet that allows users to calculate normative values for the 9 AVP structures of key interest is provided as supplementary material.